Spatial Justice and Cohesion: The Role of Place-Based Action in Community Development - Matti Fritsch; Petri Kahila; Sarolta Németh; James W. Scott (Routledge, 2024)
Place-based strategies are widely discussed as powerful instruments of economic and community development. In terms of the European debate, the local level – cities, towns and neighbourhoods – has recently come under increased scrutiny as a potentially decisive actor in Cohesion Policy. As understandings of socio-spatial and economic cohesion evolve, the idea that spatial justice requires a concerted policy response has gained currency. Given the political, social and economic salience of locale, this book explores the potential contribution of place-based initiative to more balanced and equitable socio-economic development, as well as growth in a more general sense. The overall architecture of the book and the individual chapters address place-based perspectives from a number of vantage points, including the potential of achieving greater effectiveness in EU and national level development policies, through a greater local level and citizens' role and concrete actions for achieving this; enhancing decision-making autonomy by pooling local capacities for action; linking relative local autonomy to development outcomes and viewing spatial justice as a concept and policy goal. The book highlights, through the use of case studies, how practicable and actionable knowledge can be gained from local development experiences. This book targets researchers, practitioners and students who seek to learn more about place-based based development and its potentials. Its cross-cutting focus on spatial justice and place will ensure that the book is of wider international interest.
Keywords: 300; CCLD; cohesion; European Cohesion Policy; LEADER; place-based development; regional and local autonomy; Spatial justice; territorial development